Rosai-Dorfman Disease with Intracrnial Involment in a Young Female - Fatima, Maryam; Sheikh, Ahmareen Khalid; Tanwan, Ashok Kumar (International Journal of Pathology, 2018)
Abstract: Sinus histiocytosis with massive lymphadenopathy (SHML) or Rosai Dorfman Disease (RDD) is an uncommonbenign, idiopathic disease that mimics lymphoma clinically. Strong clinical suspicion is required to diagnose this disease.Laboratory investigations may be non-specific. RDD most commonly affects lymph nodes, but extranodal involvement ofmultiple organs has been reported in literature. CNS involvement by RDD is an uncommon finding and may mimicmeningioma radiologically. Histopathology is the gold standard for the confirmation of diagnosis. Histological diagnosis isobtained after incisional biopsy or excision of the lesion. We report a case of a young girl who presented with massive bilateralcervical lymphadenopathy and headache. MRI brain showed extra-axial, lobulated right CP angle mass. Her CSF examination,Fine needle aspiration cytology of cervical lymph nodes and excision biopsy of one lymph node showed histological hallmarkof RDD, which is lymphophagocytosis or emperipolesis displayed by the histiocytes. Controversy exists about the etiologyand pathogenesis of RDD. It has a relapsing and remitting clinical course and therefore therapeutic management varies withthe clinical presentation of the patient.